PENGGUNAAN MEDIA PERMAINAN SUNDA MANDA ARENA BUNGA MATAHARI UNTUK MENGENALKAN BANGUN DATAR PADA MATA PELAJARAN MATEMATIKA - Maulida Khafidoh (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2020)
The media of sunda manda learning is the intermediary used by the teacher in delivering mathematics learning material of plane class II SD/MI by introducing the type and nature of the form of plane in a traditional game, which is applied Sundanese in the games of sunflower that contains of plane build component namely triangular, irregular hexagon, and square. By playing while learning hopefully students will be more enthusiastic in receiving learning materials and patents in the memory of students. The research methods used are qualitative research methods, and types of research actions. To obtain the research data, researchers use three data collection techniques: observation, interviews, documentation. Based on qualitative analysis results showed enthusiasm and interest in learning the flat build material with good student attitude and learning outcomes. The results of this research are important as a new study in finding mathematics learning Media on SD/MI flat build material.